Da reserva do possível à máxima efetividade: uma reflexão hermenêutica sobre a concretização dos direitos fundamentais sociais - Gladston Bethonico Bernardes Rocha Macedo (2017)
The reserve of the possible figures in the Brazilian legal discourse as an alleged impediment to the maximum effectiveness of the fundamental social rights. However, the movement of reception of this concept by the Brazilian constitutional doctrine shows the loss of the original relation with the normative nucleus to which it refers, converting its invocation into a perverse "magical mote", capable to, by itself, apophantically deprive the positive benefits claimed of its effectiveness, unconstitutionally removing the interpreters from the necessary burden of justification of their decisions. Thus, the above dissertation intends to proceed with a phenomenological repositioning of the question of the reserve of the possible, with a focus on Martin Heidegger's ontophenomenology and Hans-Georg Gadamer's philosophical hermeneutics, the theoretical framework of this study. Friedrich Müller's normativestructuring theory, Ronald Dworkin's conception of rights as trumps, and Peter Häberle's notion of essential content are reflected in the light of such framework, with the scope of affirming the application of the fundamental social rights as a process of concretization, linked to the constitutional positivity and unsusceptible of obstruction by pragmatic and economic arguments layoffs of normative foundation. The alleged reserve of the financially possible is revealed in its illegitimate pre-understandings, eristically poured into the neoliberal phallus as an instrumentalized statement to the suppression of the normative force of social rights. The budgetary impacts of the judicial implementation of positive benefits are hermeneutically resolved as a process of immanent delimitation of the essential content of fundamental rights, to be tailored in the light of its systematic links with other constitutional norms and in view of the unrepeatable uniqueness of the current historical-linguistics moment. Therefore, the application of fundamental rights can never disregard the normative otherness that is intentionally imposed, linking all arguments tending to the punctual denial of a vindicated social right.